2009
DOI: 10.1016/j.scriptamat.2009.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced phase transformation in nanocrystalline UO2

Abstract: We report a stress-induced phase transfonnation in stoichiometric U02 from fluorite to a-Pb02 structure using molecular dynamics (MD) simulations and density functional theory (DFT) calculations. MD simulations, performed on nanocrystalline microstructure under constant-stress tensile loading conditions, reveal a heterogeneous nucleation of a Pb02 phase at the grain boundaries followed by the growth of this phase towards the interior of the grain. The DFT calculations confinn the existence of the a-Pb02 struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
(6 reference statements)
4
16
1
Order By: Relevance
“…Under compressive pressure, recent DFT calculations have shown that UO 2 can take several metastable phases [35,36]. While under tensile state, recent MD simulations using the same potential found that UO 2 transforms from Fluorite phase to Scrutinyite phase, and the results are validated by DFT calculations [17]. The Rutile phase of UO 2 has never been reported before, even though the coexistence of Rutile and Scrutinyite phases has been observed both in experiments and simulations on TiO 2 [37,38].…”
Section: Crack Tip Deformation Mechanisms For the (1 1 1) Crackmentioning
confidence: 66%
See 2 more Smart Citations
“…Under compressive pressure, recent DFT calculations have shown that UO 2 can take several metastable phases [35,36]. While under tensile state, recent MD simulations using the same potential found that UO 2 transforms from Fluorite phase to Scrutinyite phase, and the results are validated by DFT calculations [17]. The Rutile phase of UO 2 has never been reported before, even though the coexistence of Rutile and Scrutinyite phases has been observed both in experiments and simulations on TiO 2 [37,38].…”
Section: Crack Tip Deformation Mechanisms For the (1 1 1) Crackmentioning
confidence: 66%
“…This potential was selected from the many available UO 2 empirical potentials because a recent comparison shows that the rigid ion type potentials with non-formal charges give better descriptions than others [15,16]. Furthermore, the Basak potential has successfully predicted the Fluorite to Scrutinyite phase transformation under tensile deformation, in reference to density-functional-theory (DFT) calculations [17,18]. The surface energies calculated using the Basak potential are 1.02 and 1.85 J/m 2 for the {1 1 1} and {1 1 0} surfaces respectively, in good agreement with previous MD simulations [19] using the Catlow potential [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 We first construct an idealized hexagonal columnar nanocrystalline microstructure unit with the Voronoi tessellation method. 7,8,31 It contains six grains of identical hexagonal shape and diameter within the three-dimensional ͑3D͒ periodic cell. We choose a grain diameter of about 13 nm for exploring the GB void nucleation under given loading conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A similar strain-induced phase transformation has been previously observed in fluoritebased nanocrystalline UO 2 providing some support to these recent observations. 121 On a broader view, the strain-induced phase transformations could be also expected in other materials, and future investigations are required to understand such structure-property relationships, and their effect on oxygen diffusion near interfaces.…”
Section: Near-interface Phase Transitionmentioning
confidence: 99%